Comparison of the Aesthetic Results of Two Common Incisions in External Rhinoplasty: A Randomized Trial. Issue 4 (July 2016) - Saedi, Babak; Amali, Amin; Taibnama, Narges; Most, Sam P.
Objective: To compare the scar outcomes of two common incisions (inverted V and stair step) by using a validated scar-outcome instrument via a randomized clinical trial. Methods: Fifty-eight consecutive cases of external rhinoplasty were randomly divided into two groups according to the type of incision. These patients were followed-up for 1 year, and the columellar scar was analyzed by using the Stony Brook Scar Evaluation Scale (SBSES) and visual analog scale (VAS) scores by an independent reviewer. Results: Of 58 patients, 28 received the inverted V and the rest received the stair-step incision. Thirty-four participants (58.6%) were women. The mean (standard deviation) age of the participants was 26.2 ± 6.6 years. After 1 month, the scar outcome was significantly better in patients with the stair-step incision (p = 0.001) by using the SBSES, but the same was not true after 1 year (p = 0.425). However, when the VAS instead of the SBSES was used to evaluate the scar, the inverted V received a better score after 12 months in this series (p = 0.005). Conclusion: Despite the better aesthetic outcome of the stair-step incision in the first month after the surgery, there was no significant difference between the two incisions after 1 year. However, in this series, when the VAS instead of the SBSES was used to evaluate the scar, the inverted V received a better score after 12 months.